DESAIN PENGENDALIAN KECEPATAN MOTOR INDUKSI 3 PHASE DENGAN PID KONTROLLER - Zulfatman, . (Jurnal Gamma, 2006)
This research considered to study how to control the dynamic changing of induction motor speed, if there were various loads or inputs from out of system by using PID Controller. Every changing of loads on induction motor caused the changing of speed perform of induction motor and system specification. Therefore, there were several changing on values of Kp, Ki and Kd components of PID Controller. Every component of PID Controller was designed for every dynamic changing of output signal of induction motor, that could use to prepare it's specification such as rise time (tr), steady time (ts) and maximum overshoot (Mp) depending on system perform that have wanted to design. The results of analysis from modeling system and PID Controller design simulated by using Matlab 6.5 and Simulink. Various of load were based on five load conditions when induction motor move in normal condition below it's full load, full load, 100% over full load, 200% over full load and 300% over full load.  The simulation indicated that even though there were several various loads in five different conditions, induction motor can move in good perform and the speed can keep well.  That was indicated by results of simulation, especially such as rise time (tr), steady time (ts) and maximum overshoot (Mp) were better than without PID Controller